Endocarditis and myocardial abscess caused by group B Streptococcus. Issue 4 (August 2015) - Bettenhausen, Aaron; Sander, Jared; Carson, Paul; Koponen, Mark; Dyke, Cornelius
Abstract : Introduction: Group B Streptococcus (GBS) is a rare infectious endocarditis. Patients with GBS infective endocarditis have a high rate of local and systemic complications. Case presentation: A 30-year-old male presented to the Emergency Department with fever, chills, fatigue and a recent onset of symptoms suggestive of stroke following a bout of pyelonephritis. Echocardiography confirmed a diagnosis of endocarditis and blood cultures grew GBS. Antibiotic therapy was initiated with penicillin G and gentamicin. Urological evaluation revealed a urethral stricture. He was taken to the operating room on hospital day 10 for the debridement of his aortic annulus, reconstruction of his aortic root and replacement of his aortic valve. On post-operative day 7, he died of sudden cardiac arrest. A large myocardial abscess located within the interventricular septum was identified post-mortem. Conclusion: Recurrent or complicated urinary tract infections are rare among the young male population. Without evaluation and treatment for the underlying pathology, patients are at risk of developing antimicrobial-resistant infections, which may disseminate rapidly. Although a common pathogen of the urinary tract, GBS is a rare infectious agent for endocarditis. We propose urethral stricture as a risk factor for developing GBS endocarditis. Operative timing for these infections can be challenging; however, urgent and radical surgical debridement appears to yield favourable results.